Neural cue reactivity is not stronger in male than in female patients with alcohol use disorder - Gerhardt, Sarah; Hoffmann, Sabine; Tan, Haoye; Gerchen, Martin Fungisai; Kirsch, Peter; Vollstädt-Klein, Sabine; Kiefer, Falk; Bach, Patrick; Lenz, Bernd (Frontiers in behavioral neuroscience, 2022)
BackgroundMales consume more alcohol than females, and alcohol use disorder (AUD) is more prevalent in males than females. However, females progress faster to AUD. Sex differences in neural alcohol cue reactivity were previously observed in young social drinkers, indicating a role of hypersensitivity to alcohol-related cues in very early stages of addiction. To our knowledge, this is the first study on patients diagnosed with AUD to test sex differences in neural reactivity to alcohol cues in order to widen previous findings.MethodsWe analyzed data from previous studies, using a well-established functional magnetic resonance imaging (fMRI) paradigm to compare neural reactivity to alcohol cues between 42 female and 124 male patients with AUD (mean age 45 and 46 years) in predefined regions of interest that were implicated by previous studies (ventral and dorsal striatum as well as caudate, putamen, amygdala, hippocampus, insula, anterior cingulate cortex, and medial prefrontal cortex) using independent samples t-tests. Post-hoc, effect size calculations were performed.ResultsThroughout all nine regions of interest, we found no statistically significant sex differences in neural reactivity toward alcoholic pictures alone or in comparison to neutral pictures (p > 0.05, FDR-corrected). Post-hoc effect size estimates indicated a magnitude between 0.137 and 0.418 (Hedge’s g) on alcohol reactivity to alcohol cues compared to neutral cues and indicate very small to less than medium effect sizes in the direction of higher cue reactivity in female patients.ConclusionPrevious studies showed sex differences in neural alcohol cue reactivity in younger social and problematic alcohol drinkers, i.e., stronger striatal cue-reactivity in males. After correction for multiple comparisons, we did not observe significant sex differences in a cohort of middle-aged females and males with AUD. Sex differences that are present during early phases of addiction development might disappear at later stages of AUD and might thus be considered as clinically less relevant in patients with more severe AUD.
Gesehen am 19.12.2022